Effect of Silicone Hydrogel Contact Lenses on Stability of Cellular and Intracellular Membranes in Corneal Epithelium (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Contact lenses are increasingly used worldwide for correcting refraction disorders. However, contact lenses can destroy a biochemical composition of the tear.Purpose. To determine the effect of silicone hydrogel contact lenses on the stability of cell membranes and membranes of subcellular structures in the corneal epithelium through detecting marker enzymes in the tear fluid.Material and Methods. We determined the activity of lactate dehydrogenase, glucose-6-phosphate dehydrogenase, and acid phosphatase in tears of patients divided into two groups. Study group comprised 13 people (24 eyes): moderate myopia patients continuously wearing soft contact lenses. Control group consisted of 20 people (40 eyes): moderate myopia patients, spectacles wearers.Results. We revealed a significant increase in the activity of lactate dehydrogenase and glucose-6-phosphate dehydrogenase by >35% and 24%, respectively, as well as a significant increase in the activity of acid phosphatase by 22.4% in the Study group patients comparing to controls.Conclusions. Continuous soft contact lens wearing increases the lability of the corneal epithelium cell membranes. We believe that pharmacological correction of such pathologic changes can prevent the development of severe complications associated with contact lens vision correction.
Keywords: cornea; contact lens; lactate dehydrogenase; glucose-6-phosphate dehydrogenase; acid phosphatase